‘“O pierlesse Poesye, where is then thy place?”’: Locating Patronage in Spenser’ - McCabe, R (University of Chicago Press, 2018)
“O pierlesse Poesye, where is then thy place?”: As Piers’s despairing question indicates, Spenser’s concern with patronage stretches beyond the customary “topoi” of his paratexts to inform the topography of the verse through which he seeks it. As he proceeds from genre to genre, the geographical dislocation of his speakers figures the cultural displacement of his craft. In terms of the authorial careers he lived and fabricated—the distinct yet inextricably related careers of Edmund Spenser and Colin Clout—“place” is of crucial thematic significance to “authority,” whether it be Leicester House, Kilcolman Castle, Essex House, Mount Acidale, or the “courts” of Cynthia and Mercilla (and it is arguable whether the former three are any less fictive than the latter). Beginning with an analysis of the “place” of poetry in the pastoral landscape of The Shepheardes Calender, this article examines its various inflections through the genera that followed. Relegated to the allegedly “salvage” terrain of the Gaelic bards, Spenser creates landscapes that both attest to, and simultaneously resist, his fear of cultural assimilation. But the wish to live in fairyland, expressed in the proem to the sixth book of The Faerie Queene, concedes poetry’s inability to fashion a patronal culture worthy of heroic verse, and necessitates the adoption of an Ovidian poetics paradoxically centered on the displaced self and the “designer” wilderness it inhabits.